Respon Pertumbuhan dan Hasil Tanaman Kacang Tanah Pada Aplikasi Biochar Bambu - Kadek Suparta; Luh Kartini; Yohanes Parlindungan Situmeang (GEMA AGRO, 2018)
This study aims to determine the effect of bamboo biochar dose on the growth and yield of peanut crops. This study used a randomized block design with one factor. The tested treatments were dosage of biochar fertilizer with 4 dosage levels and one treatment without biochar dose (control), with the treatment arrangement as follows: without biochar, 4 ton ha-1, 8 ton ha-1, 12 ton ha-1, 16 ton ha-1. This treatment was repeated 3 times to obtain 15 plot experiments. The results showed that the biochar dose treatment had significant effect on all observed variables, except the variable of plant height and maximum number of leaves per plant had no significant effect. The highest yield of dry seed oven of seeds per plant was obtained in the dosage of 4 ton ha-1 biochar dose of 21.83 g, an increase of 111.81% compared with no biochar 10.33 g. Based on regression analysis, the optimum dosage of biochar is 7.50 ton ha-1, with dry weight of oven seed per plant maximum 19.03 g.